Between Rhetoric and Reality : The State and Use of Indigenous Knowledge in Post-Colonial Africa - Awuah-Nyamekye, Samuel; Mawere, Munyaradzi (Book collections on Project MUSE., 2015)
Since time immemorial, indigenous peoples around the world have developed knowledge systems to ensure their continued survival in their respective territories. These knowledge systems have always been dynamic such that they could meet new challenges. Yet, since the so-called enlightenment period, these knowledges have been supplanted by the Western enlightenment science or colonial science hegemony and arrogance such that in many cases they were relegated to the periphery. Some Euro-centric scholars even viewed indigenous knowledge as superstitious, irrational and anti-development. This erroneous view has, since the colonial period, spread like veld fire to the extent of being internalised by some political elites and Euro-centric academics of Africa and elsewhere. However, for some time now, the potential role that indigenous peoples and their knowledge can play in addressing some of the global problems haunting humanity across the world is increasingly emerging as part of international discourse. This book presents an interesting and insightful discourse on the state and role that indigenous knowledge can play in addressing a tapestry of problems of the world and the challenges connected with the application of indigenous knowledge in enlightenment science-dominated contexts. The book is not only useful to academics and students in the fields of indigenous studies and anthropology, but also those in other fields such as environmental science, social and political ecology, development studies, policy studies, economic history, and African studies.